Analyzing the Influence of the 4A Tourism Components on Visitor Satisfaction at the Jakarta Wayang Museum - David Andrean; Vishnuvardhana S. Soeprapto (LP2M IAIN Palopo, 2026)
The revitalization of the Jakarta Wayang Museum has enhanced its role as a cultural heritage tourism destination; however, the extent to which its tourism components influence visitor satisfaction has not been empirically examined. Purpose: This study aims to analyze the effect of the 4A tourism components—attractions, accessibility, amenities, and ancillary services—on visitor satisfaction at the Jakarta Wayang Museum. Methods: A quantitative explanatory research design with a cross-sectional survey approach was employed. Data were collected through structured questionnaires administered to 100 visitors selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS version 25, following tests of validity, reliability, and classical assumptions. Results: The results indicate that attractions (t = 4.475; p < 0.001), accessibility (t = 4.081; p < 0.001), amenities (t = 4.918; p < 0.001), and ancillary services (t = 3.648; p < 0.001) each have a positive and significant effect on visitor satisfaction. Simultaneously, the four variables significantly influence visitor satisfaction (F = 18.420; p < 0.001). The coefficient of determination (R² = 0.437) demonstrates that 43.7% of the variance in visitor satisfaction is explained by the 4A tourism components. Among the variables examined, amenities emerged as the most influential factor. These findings confirm the relevance of the 4A tourism framework in evaluating destination quality within cultural tourism settings. Implications: The study implies that museum managers should prioritize improvements in visitor facilities and comfort while maintaining attractive cultural experiences, accessibility, and supporting services to enhance visitor satisfaction and destination competitiveness.